2022
DOI: 10.1155/2022/5479626
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Serum Homocysteine, Vitamin B12, and Folic Acid Levels with Papulopustular Rosacea Severity: A Case-Control Study

Abstract: Background. Rosacea is a chronic inflammatory skin disease with a multifactorial etiology. Recently, associations between serum homocysteine (Hcy) levels and inflammatory skin diseases, such as psoriasis and hidradenitis suppurativa, have been reported. However, no study has explored the levels of serum Hcy, folic acid, and vitamin B12 in patients with rosacea. Objective. To investigate serum Hcy, vitamin B12, and folic acid levels in patients with papulopustular rosacea (PPR), we characterized the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…When conventional treatments do not affect the disease, the use of β-blockers can be promising, especially propranolol which can be very effective in treating the disease [14-16].Thus, in this study, the effect of propranolol on the treatment of rosacea was investigated, and the results showed that the mean age of the patients was 46.65±10.38 years, and most of them were women (65.2%). These findings are close to that found byChung et al, 2022 in Korea, who found the mean age of the patients was 45 years and most of them were women[17]. While Suggs et al, 2020 found that most patients were females, however, the mean age of the patients was 51 years, which was higher than that observed in this study[18].…”
supporting
confidence: 86%
“…When conventional treatments do not affect the disease, the use of β-blockers can be promising, especially propranolol which can be very effective in treating the disease [14-16].Thus, in this study, the effect of propranolol on the treatment of rosacea was investigated, and the results showed that the mean age of the patients was 46.65±10.38 years, and most of them were women (65.2%). These findings are close to that found byChung et al, 2022 in Korea, who found the mean age of the patients was 45 years and most of them were women[17]. While Suggs et al, 2020 found that most patients were females, however, the mean age of the patients was 51 years, which was higher than that observed in this study[18].…”
supporting
confidence: 86%